Where is sport science? Self-reported training methods of mixed martial arts athletes and coaches during fight-camp - Batra, A. (Sport Performance & Science Reports, 2019)
In recent years mixed martial arts (MMA) has experienced unprecedented growth re ected by its rise in professionalism, making it a highly popular global sport (1, 2). Alongside there is increased interest and demand for knowledge on evidence { based practices in MMA and the best examples are the new UFC Performance Institutes built in Las Vegas (2017) and Shanghai (2019) ($14 and $13 milion investments, repectively) focusing on research and on developing new standards for optimum athletic performance in combat sport athletes. Despite the popularity of MMA it is uknown what training methods are utilized by MMA coaches and athletes and to what extent they use scienti c data (evidence-based approach) to enhance performance on a daily basis (3). This is a limiting factor for professionals engaged in the physical preparation of MMA athletes and for sport scientists whose goal should be publishing applied and relevant research (4,5). Based on anecdotal evidence and author experience in combat sports environment it is known that head coach is often perceived as "all knowing" about every facet of their discipline when, in fact, they typically are not formally educated or well-trained in current methods of enhancing sport performance. Particularly in those martial arts which are not severed from their historical roots such as judo, taekwon-do, karate where grade designates the hierarchy, and in turn, "master" has always the right to the last word. It should be considered that while the head coach has some training and experience in the concepts and subtleties of the sport (particularly as it relates to technique and tactics) holistically they are typically untrained or poorly trained in evidence-based strength and conditioning methods (6). Therefore the purpose of this study is to reveal that evidence-based strength and conditioning (S&C) and sport science is poorly understood and implemented by MMA athletes' and coaches.